Strategic Human Resource Management and Performance: A Literature Review - Slamet Sutrisno; Martinus Tukiran; Erna Herlina; Reza Suriansha; Imam Rosyadi (Budapest International Research and Critics University, 2022)
The purpose of this article is to conduct an analysis through a literature review of 3 (three) reputable international journal papers related to the contribution of strategic human resource management to company performance, which aims to describe and identify the impact factors of strategic human resource management on performance in international companies. The method used is a systematic literature review of 3 (three) papers published in international journals with the stages of searching for journals through Publish or Perish (PoP), then theme selection and categorization, comparison, apostheory synthesis and conclusion drawing. The results of a systematic literature review show that the implementation of strategic human resource management that is in line with organizational goals in the company can provide a significant impact factor on the performance of international companies, especially in the regions of Kenya, Turkey and the United Kingdom (UK). And it can be synthesized from the author's perspective that strategic human resource management is related to the role of human resource management systems in company performance, especially focusing on aligning human resources as a means to gain competitive advantage and organization performance, namely the function of people, processes and technology.